A German Digital Grand Strategy: Integrating Digital Technology, Economic Competitiveness, and National Security in Times of Geopolitical Change - Tyson Barker; David Hagebölling (German Council on Foreign Relations (DGAP), 2022)
This report systematically outlines the state of play in digital policy and Berlin's current policy approach. It provides 48 recommendations for strengthening Germany's efforts to build a confident, high-performing European digital economy embedded in an open, democratic, and rules-based digital order.
Keywords: F5; O3; L5; L63; 330; Digital Policy; Digital Technology; Economic Competitiveness; National Security; Foreign Policy; International Politics; International Relations; Geopolitics; European Union; Germany; Grand Strategy; Diplomacy